'Balloon pressure technique' for endovascular treatment of spinal cord arteriovenous fistulas: preliminary results in 10 cases. (28th April 2022) - Clarençon, Frédéric; Parat, Damien; Shotar, Eimad; Premat, Kévin; Lenck, Stéphanie; Drir, Mehdi; Maillart, Elisabeth; Boch, Anne-Laure; Sourour, Nader
Abstract : Background: Spinal arteriovenous fistulas (SAVFs) are challenging lesions to treat by endovascular means. Our purpose was to report our early experience with dual lumen balloons (DLBs) for embolization of SAVFs using ethylene vinyl alcohol (EVOH) (the so-called 'balloon pressure technique' (BPT)). Materials and methods: During the inclusion period, 10 consecutive patients (nine men, mean age 61.6 years) underwent endovascular treatment of a SAVF (seven dural SAVFs and three epidural SAVFs) at a single institution using the BPT. DLBs were used in all cases. In seven cases (70%), a regular DLB was used, while in three cases (30%), low profile DLBs were used. EVOH was used as the liquid embolic agent in all cases. Technical and clinical complications were systematically recorded. Clinical and angiographic outcomes were systematically evaluated more than 3 months after the procedure. Results: Complete cure of the SAVF by endovascular means alone was obtained in 80% of cases (8/10). For the two patients with incomplete SAVF occlusion, surgery was successfully performed secondarily. No recurrence was found at the 3 month follow-up in the eight patients for whom complete occlusion was obtained at the end of the embolization procedure. No permanent clinical complication was recorded using the BPT. Clinical improvement was observed in 6/10 (60%) cases. Conclusion: BPT was a feasible technique, with regular or low profile DLBs, for embolization of SAVFs. Our preliminary results suggest the safety and effectiveness of this technique.